Network Neutrality and Quality of Service: A two-sided market analysis - Emin Köksal (International Telecommunications Society (ITS), 2010)
In this paper, we examine welfare implications of switching from a neutrality regime to a network management regime. While in the former a network provider or an integrated ISP should transmit data with a-bit-is-a-bit principle, in the latter it is allowed to differentiate its connection quality considering economic value of data packets transmitted from content or application providers to end-users. The differentiation indicates allowing the ISP to apply QoS arrangements for quality-sensitive contents or applications. The above issues are first examined with a model in which there is a monopolist ISP, and later it is extended through introducing duopoly competition. Our results refer some potential gains that can be captured through network management regime. Although the overall effect of deviation from neutrality regime on total surplus may not defined clearly, both in monopoly and in duopoly models we have found that end-users and quality-sensitive content or application providers benefit from network management regime, in case of enough increase in quality of connection offered by ISP(s).And, regular content or application providers suffer with decreasing connection quality because of fixed network capacity.
Keywords: L12; L13; L15; L51; L96; 330; Telecommunications; Internet; Network Neutrality; Network Management Two-Sided Market; Quality of Service